High-entropy electrolyte for lithium ion battery, electrolyte preparation method and battery

By using high-entropy electrolyte in lithium-ion batteries and using a combination of a variety of lithium salts and organic solvents to form a high-entropy structure, the problems of fast charging and long cycle life of lithium batteries under extreme conditions are solved, and excellent electrochemical performance and economical preparation process are achieved.

CN119920978APending Publication Date: 2025-05-02SOUTHEAST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411924952.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing lithium-ion battery fast charging solution cannot meet the needs of fast charging and long cycle life of lithium batteries under extreme conditions, and the impact of additives on the entire life cycle is limited.

Method used

High-entropy electrolyte is used, consisting of a variety of lithium salts and organic solvents. By simply introducing a variety of lithium salts, the inorganic anions in the electrolyte are more involved in the inner solvation sheath layer, forming a high-entropy structure, and reducing the diffusion energy barrier and interface migration energy barrier of lithium ions in the electrolyte.

Benefits of technology

The excellent performance of lithium-ion batteries under fast charging and extreme conditions, including high Coulomb efficiency, long cycle life and good electrochemical properties, while avoiding the need for additional additives, diluents and co-solvents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920978A_ABST
    Figure CN119920978A_ABST
Patent Text Reader

Abstract

The invention relates to a high-entropy electrolyte for a lithium ion battery, an electrolyte preparation method and a battery, the high-entropy electrolyte for the lithium ion battery is composed of a plurality of lithium salts and an organic solvent, and is used for improving the dynamic migration process of lithium ions in the electrolyte; the organic solvent is at least one of an ester solvent, an ether solvent and an ether-ester blended solvent; and the total concentration of the various lithium salts in the organic solvent is 1.0-2.0 mol / L. Compared with the prior art, the high-entropy electrolyte system disclosed by the invention can be used for the lithium ion battery, and inorganic anions in the electrolyte can participate in an inner-layer solvation sheath layer more by simply introducing various lithium salts without any additive, diluent or cosolvent, so that the high-entropy electrolyte system can be used for the lithium ion battery. Moreover, richer and diversified solvated cluster configuration, namely a so-called high-entropy structure, is presented, so that a diffusion energy barrier of lithium ions in an electrolyte and a migration energy barrier of the lithium ions at an interface are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a high entropy electrolyte for lithium ion batteries, a method for preparing the electrolyte, and a battery. Background Art

[0002] Lithium secondary batteries play an indispensable and important role in the fields of consumer electronics, electric vehicles and energy storage systems, and will continue to play a key role in the foreseeable future. Entropy regulation has shown great potential in the field of materials science, among which "high entropy alloys" are a typical and successful example: by significantly increasing the configurational entropy, the enthalpy of formation of undesirable intermetallic compounds can be effectively counteracted, thereby obtaining high entropy alloys with excellent performance and novel properties. Changes in entropy and enthalpy can describe most thermodynamic processes, whether spontaneous or non-spontaneous. From a thermodynamic perspective, especially from the perspective of entropy, analyzing the relationship between electrolyte engineering and performance not only provides a unique research perspective for understanding material design, but also brings the possibility of breaking through the limitations of the design principles of conventional electrolytes under extreme conditions. As the core component of conducting ions in batteries, electrolytes play a vital role in realizing the expansion of battery application scenarios from conventional conditions to extreme conditions (such as extremely high / low temperatures, high voltages and ultra-fast charging). However, extreme conditions place more stringent requirements on the chemical / electrochemical stability and ion transport performance of electrolytes. To this end, researchers have proposed a variety of solutions for lithium batteries to break through the above limitations:

[0003] In traditional commercial electrolytes composed of lithium hexafluorophosphate and carbonate solvents, the solvent usually forms a strong solvation structure with lithium ions, that is, a solvation form in which the central lithium ion is highly coordinated with the surrounding solvent molecules. The CEI and SEI derived from this type of electrolyte at the positive and negative electrode interfaces of the battery are often composed of organic components such as polycarbonate oligomers and alkyl lithium carbonate obtained by redox decomposition of the solvent. This interface film structure often has low ion conductivity, loose structure, and poor uniformity. By adding a certain amount of additives to the electrolyte, the physical and chemical properties of the interface film, such as the ratio of inorganic and organic components, can be regulated to a certain extent. For example, lithium bis(oxalatoborate) (LiBOB) and dopamine (DA) are added to improve the fast charging performance of lithium-ion batteries (NanoEnergy, 2021, 88: 106301). However, although additives can change the properties of the interface film, their effect on the entire life cycle of the lithium battery is limited, and they often do not have outstanding advantages in the long cycle life of the battery. The high-concentration electrolyte prepared by increasing the concentration of lithium salt can make Li +The desolvation activation energy is greatly reduced, and the anion-derived inorganic negative electrode interface can enable the battery to have fast charging performance and reduce the side reactions between the electrode and the electrolyte (J.Am.Chem.Soc., 2014, 136(13):5039; Chem.Commun., 2013, 49(95):11194). However, this method requires the use of a large amount of lithium salt, and due to its poor economic efficiency, it is impossible to achieve reasonable practical application of lithium batteries.

[0004] This shows that the current research on fast-charging electrolytes cannot meet the actual application needs of lithium batteries. Summary of the invention

[0005] The purpose of the present invention is to provide a high entropy electrolyte for lithium ion batteries, a method for preparing the electrolyte and a battery in order to overcome the defects of the above-mentioned prior art. The high entropy electrolyte system in the present invention is used for lithium ion batteries. Without the need for any additives, diluents or co-solvents, the excellent rate performance of lithium ion batteries can be achieved by simply introducing a variety of lithium salts, thereby achieving fast charging.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] The first aspect of the present invention provides a high entropy electrolyte for a lithium ion battery, wherein the high entropy electrolyte for a lithium ion battery is composed of a plurality of lithium salts and an organic solvent, and the high entropy electrolyte for a lithium ion battery is used to improve the kinetic migration process of lithium ions in the electrolyte;

[0008] The organic solvent is at least one of an ester solvent, an ether solvent, and an ether-ester blend solvent;

[0009] The total concentration of various lithium salts in organic solvents is 1.0-2.0 mol / L;

[0010] The lithium salt is selected from at least five of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium trifluoroacetate, and lithium nitrate.

[0011] Furthermore, the organic solvent is selected from at least two or more of vinylene carbonate, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, triethyl phosphate, trimethyl phosphate, ethyl methyl carbonate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, ethyl butyrate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and 1,3-dioxolane.

[0012] Furthermore, the lithium salt in the electrolyte promotes the decomposition of the organic solvent on the surface of the negative electrode to form a SEI rich in F, B, P, S, and N inorganic components, so that the lithium battery adapted to the electrolyte has excellent fast charging performance at room temperature.

[0013] Furthermore, the water content in the high entropy electrolyte for lithium-ion batteries is less than 1 ppm.

[0014] The second aspect of the present invention provides a method for preparing a high entropy electrolyte for a lithium ion battery as described above, comprising the following steps: in an inert argon atmosphere, mixing the lithium salt and the organic solvent in the high entropy electrolyte for a lithium ion battery evenly to obtain a high entropy electrolyte for a lithium ion battery.

[0015] Further preferably, the specific process of uniformly mixing the lithium salt and the organic solvent in the high entropy electrolyte for lithium-ion batteries is: mixing the organic solvent and the lithium salt, and stirring for 8 hours at 40° C. using a magnetic heating stirrer to fully dissolve the lithium salt to form a homogeneous solution.

[0016] A third aspect of the present invention provides a battery, wherein the electrolyte used in the battery is the high entropy electrolyte for lithium ion batteries described above or the high entropy electrolyte for lithium ion batteries prepared according to the method for preparing the high entropy electrolyte for lithium ion batteries described above.

[0017] Further, the positive electrode of the battery includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide;

[0018] The negative electrode of the battery includes one or more of graphite, hard carbon, silicon negative electrode, silicon-carbon negative electrode, silicon-graphite negative electrode, and silicon monoxide.

[0019] Furthermore, the separator of the battery is made of one of polyethylene, polypropylene, PP / PE / PP three-layer composite film, and glass fiber separator.

[0020] Furthermore, the positive and negative electrode capacities of the battery are matched, that is, the ratio of the negative electrode capacity to the positive electrode capacity of the battery is 1.10-1.15, so as to ensure that the negative electrode material has sufficient capacity to accept the lithium ions released by the positive electrode material during charging, and avoid the lithium ions from being precipitated on the negative electrode surface in the form of dead lithium.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention provides a high entropy electrolyte for lithium-ion battery fast-charging electrolyte, which can reduce the migration energy barrier and interface impedance of lithium ions in the electrolyte and improve the kinetic process of lithium ion migration in the electrolyte.

[0023] 2. The present invention specifically combines lithium salts and solvents in high-entropy electrolytes for lithium-ion batteries and further optimizes the concentration and ratio. Due to the diversity of components, it has stronger designability, so that the electrolyte added to the present invention can have excellent compatibility and rate performance with a variety of positive and negative electrodes.

[0024] 3. The high entropy electrolyte for lithium-ion batteries described in the present invention simply introduces a variety of lithium salts without the need to introduce any additional additives, diluents, or co-solvents, so that the inorganic anions in the electrolyte participate more in the inner solvation sheath layer, thereby reconstructing a richer and more diverse solvation cluster configuration, the so-called high entropy structure, thereby reducing the diffusion energy barrier of lithium ions in the electrolyte and the migration energy barrier at the interface, and the SEI derived from the negative electrode interface presents inorganic components rich in F, B, P, S, and N, so that the battery can still have good electrochemical properties under extreme conditions (fast charging).

[0025] 4. The method provided by the present invention is simple to operate, low in cost, and the pharmaceutical ingredients used are safe. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a comparison chart of polarization voltages of the high entropy electrolyte and the conventional electrolyte in the full-cell GITT test in Example 1.

[0027] Figure 2 This is a comparison chart of lithium ion diffusion coefficients fitted from the GITT test results in Example 1.

[0028] Figure 3 It is a comparison of the polarization of the positive electrode / Li during charging of the conventional electrolyte and the high entropy electrolyte in the three-electrode system in Example 1.

[0029] Figure 4 It is a performance comparison chart of the conventional electrolyte and the high entropy electrolyte in Example 1 in the full battery rate cycle test.

[0030] Figure 5 This is the SEM image of the negative electrode surface of the conventional electrolyte and the high entropy electrolyte in Example 1 after rate testing.

[0031] Figure 6 This is a SEM image of the positive electrode surface after the conventional electrolyte and the thermal responsive electrolyte in Example 1 were cycled 400 times in the full battery. DETAILED DESCRIPTION

[0032] On the whole, the electrolyte system of the present invention is composed of lithium salt and organic solvent; the lithium salt is selected from several lithium salts commonly used in various lithium batteries, and the organic solvent is a co-mixed solvent of esters, ethers or esters and ethers. Compared with conventional electrolytes, the high entropy electrolyte system used in the present invention is used for lithium-ion batteries. Without the need for any additives, diluents, or co-solvents, a variety of lithium salts are simply introduced to make the inorganic anions in the electrolyte participate more in the inner solvation sheath layer, and present a richer and more diverse solvation cluster configuration, the so-called high entropy structure, thereby reducing the diffusion energy barrier of lithium ions in the electrolyte and the migration energy barrier at the interface, and the SEI derived from the negative electrode interface presents inorganic components rich in F, B, P, S, and N, so that the battery can still have good electrochemical performance under extreme conditions (fast charging). The high entropy electrolyte of the present invention shows excellent potential in the application of lithium-ion batteries from conventional conditions to extreme conditions.

[0033] The present invention first provides a high entropy electrolyte for lithium ion batteries. The electrolyte system consists of a lithium salt and an organic solvent. The lithium salt is several types of lithium salts commonly used in lithium batteries, and the organic solvent is an ester solvent, an ether solvent or an ether-ester blended solvent.

[0034] In one embodiment of the present invention, the content of the lithium salt in the organic solvent is 1.0 to 2.0 mol / L.

[0035] In one embodiment of the present invention, the lithium salt is selected from at least five of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium trifluoroacetate, and lithium nitrate.

[0036] In one embodiment of the present invention, the organic solvent is selected from at least two or more of vinylene carbonate, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, triethyl phosphate, trimethyl phosphate, ethyl methyl carbonate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, ethyl butyrate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether or 1,3-dioxolane.

[0037] The raw materials involved in the above-mentioned method for preparing a high entropy electrolyte for lithium-ion batteries are all purchased commercially, and the equipment and processes used are well known to those skilled in the art.

[0038] In one embodiment of the present invention, the water content in the electrolyte system is less than 1 ppm.

[0039] The present invention further provides a method for preparing the high entropy electrolyte for lithium ion batteries, comprising mixing the organic solvent and lithium salt in an inert argon atmosphere, and stirring the mixture for 8 hours at 40° C. using a magnetic heating stirrer to fully dissolve the lithium salt to form a homogeneous solution.

[0040] The present invention further provides the use of the high entropy electrolyte for lithium ion batteries, and the high entropy electrolyte for lithium ion batteries is used to make batteries.

[0041] The present invention further provides a battery, wherein the electrolyte used in the battery is a high-entropy electrolyte for a lithium-ion battery or a high-entropy electrolyte for a lithium-ion battery prepared according to the method for preparing the high-entropy electrolyte for a lithium-ion battery.

[0042] In one embodiment of the present invention, the positive electrode of the battery is one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.

[0043] In one embodiment of the present invention, the negative electrode of the battery is made of one or more of graphite, hard carbon, silicon negative electrode, silicon-carbon negative electrode, silicon-graphite negative electrode, and silicon monoxide.

[0044] In one embodiment of the present invention, the separator of the battery is made of one of polyethylene, polypropylene, PP / PE / PP three-layer composite film, and glass fiber separator.

[0045] In order to make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme of the embodiment of the present invention will be clearly and completely described in conjunction with the drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. In order to more clearly state the scheme of the present application, it is described by the following embodiments. The present invention is described in detail below in conjunction with specific embodiments.

[0046] Any features such as preparation methods, materials, structures or composition ratios that are not clearly described in this technical solution shall be deemed as common technical features disclosed in the prior art.

[0047] Embodiment 1:

[0048] This embodiment provides a high entropy electrolyte for a lithium ion battery:

[0049] Ethylene carbonate and ethyl methyl carbonate were mixed evenly in a volume ratio of 3:7, and lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, and lithium nitrate were added to an organic solvent in a molar ratio of 1:1:1:1:1 to make the total salt concentration 1.0M. A magnetic heating stirrer was used to stir at 40°C for 8 hours to fully dissolve the lithium salt to form a homogeneous solution to obtain a high entropy electrolyte. At room temperature, the electrolyte system was used for full battery testing with graphite as the negative electrode and lithium nickel cobalt manganese oxide as the positive electrode. After testing, it was found that the coulombic efficiency of the battery can reach 99.7%, and at 1.63mAcm 2- At a current density of , its cycle life can reach 410 cycles, and the capacity retention rate is 85.29%.

[0050] Embodiment 2:

[0051] This embodiment provides a high entropy electrolyte for a lithium ion battery:

[0052] Fluorinated ethylene carbonate, dimethyl carbonate, and diethyl carbonate were mixed in a volume ratio of 1:4:5, and lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium trifluoromethanesulfonate, and lithium trifluoroacetate were added to an organic solvent in a molar ratio of 1:1:1:1:1 to make the total salt concentration 1.0M. A magnetic heating stirrer was used to stir at 40°C for 8 hours to fully dissolve the lithium salt to form a homogeneous solution to obtain a high entropy electrolyte. The electrolyte system was used for full battery testing with graphite as the negative electrode and lithium nickel cobalt manganese oxide as the positive electrode. After testing, it was found that the coulombic efficiency of the battery can reach 99.0%, and at 1.63mA cm 2- Its cycle life can reach 500 cycles at a current density of , and the capacity retention rate is above 80%.

[0053] Embodiment 3:

[0054] This embodiment provides a high entropy electrolyte for a lithium ion battery:

[0055] Methyl propionate and fluoroethylene carbonate were mixed evenly in a volume ratio of 1:9, and lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium trifluoromethanesulfonate, and lithium nitrate were added to an organic solvent in a molar ratio of 1:1:1:1:1 to make the total salt concentration 1.0M. A magnetic heating stirrer was used to stir at 40°C for 8 hours to fully dissolve the lithium salt to form a homogeneous solution to obtain a high entropy electrolyte. The electrolyte system was used for full battery testing with graphite as the negative electrode and lithium nickel cobalt manganese oxide as the positive electrode. After testing, it was found that the coulombic efficiency of the battery can reach 99.5%, and at 0.815mAcm 2- Its cycle life can reach 400 cycles at a current density of 1.58kWh, and the capacity retention rate is over 90%.

[0056] Embodiment 4:

[0057] This embodiment provides a high entropy electrolyte for a lithium ion battery:

[0058] Ethylene carbonate and ethyl methyl carbonate were mixed evenly in a volume ratio of 3:7, and lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, and lithium nitrate were added to an organic solvent in a molar ratio of 1:1:1:1:1 to make the total salt concentration 2.0M. A magnetic heating stirrer was used to stir at 40°C for 8 hours to fully dissolve the lithium salt to form a homogeneous solution to obtain a high entropy electrolyte. At room temperature, the electrolyte system was used for full battery testing with silicon carbon as the negative electrode and nickel cobalt manganese oxide as the positive electrode. After testing, it was found that the coulombic efficiency of the battery can reach 99.0%, and at 1.63mAcm 2- Its cycle life can reach 300 cycles at a current density of , and the capacity retention rate is above 80%.

[0059] Embodiment 5:

[0060] This embodiment provides a high entropy electrolyte for a lithium ion battery:

[0061] Fluorinated ethylene carbonate, dimethyl carbonate, and diethyl carbonate were mixed in a volume ratio of 1:4:5, and lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium trifluoromethanesulfonate, and lithium trifluoroacetate were added to an organic solvent in a molar ratio of 1:1:1:1:1 to make the total salt concentration 2.0M. A magnetic heating stirrer was used to stir at 40°C for 8 hours to fully dissolve the lithium salt to form a homogeneous solution to obtain a high entropy electrolyte. The electrolyte system was used for full battery testing with graphite as the negative electrode and lithium iron phosphate as the positive electrode. After testing, it was found that the coulombic efficiency of the battery can reach 99.8%, and at 0.815mA cm 2- Its cycle life can reach 1000 cycles at a current density of , and the capacity retention rate is above 90%.

[0062] Embodiment 6:

[0063] This embodiment provides a high entropy electrolyte for a lithium ion battery:

[0064] Methyl propionate and fluoroethylene carbonate were mixed evenly in a volume ratio of 1:9, and lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium trifluoromethanesulfonate, and lithium nitrate were added to an organic solvent in a molar ratio of 1:1:1:1:1 to make the total salt concentration 2.0M. A magnetic heating stirrer was used to stir at 40°C for 8 hours to fully dissolve the lithium salt to form a homogeneous solution to obtain a high entropy electrolyte. The electrolyte system was used for full battery testing with silicon graphite as the negative electrode and lithium cobalt oxide as the positive electrode. After testing, it was found that the coulombic efficiency of the battery can reach 99.8%, and at 1.63mA cm 2- At a current density of 1.54 W, its cycle life can reach 700 cycles, and the capacity retention rate is above 85%.

[0065] Embodiment 7:

[0066] This embodiment provides a high entropy electrolyte for a lithium ion battery:

[0067] Ethylene carbonate and ethyl methyl carbonate were mixed evenly in a volume ratio of 3:7, and lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, and lithium nitrate were added to an organic solvent in a molar ratio of 1:1:1:1:1 to make the total salt concentration 1.5M. A magnetic heating stirrer was used to stir at 40°C for 8 hours to fully dissolve the lithium salt to form a homogeneous solution to obtain a high entropy electrolyte. At room temperature, the electrolyte system was used for full battery testing with graphite as the negative electrode and lithium nickel manganese oxide as the positive electrode. After testing, it was found that the coulombic efficiency of the battery can reach 99.8%, and at 0.815mAcm 2- Its cycle life can reach 400 cycles at a current density of 1.58kWh, and the capacity retention rate is over 90%.

[0068] Embodiment 8:

[0069] This embodiment provides a high entropy electrolyte for a lithium ion battery:

[0070] Fluorinated ethylene carbonate, dimethyl carbonate, and diethyl carbonate were mixed in a volume ratio of 1:4:5, and lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium trifluoromethanesulfonate, and lithium trifluoroacetate were added to an organic solvent in a molar ratio of 1:1:1:1:1 to make the total salt concentration 1.5M. A magnetic heating stirrer was used to stir at 40°C for 8 hours to fully dissolve the lithium salt to form a homogeneous solution to obtain a high entropy electrolyte. The electrolyte system was used for full battery testing with silicon carbon as the negative electrode and lithium cobalt oxide as the positive electrode. After testing, it was found that the coulombic efficiency of the battery can reach 99.4%, and at 0.815mA cm 2- Its cycle life can reach 700 cycles at a current density of , and the capacity retention rate is above 80%.

[0071] Embodiment 9:

[0072] This embodiment provides a high entropy electrolyte for a lithium ion battery:

[0073] Ethylene carbonate and ethylene glycol dimethyl ether were mixed in a volume ratio of 1:1, and lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, and lithium trifluoroacetate were added to an organic solvent in a molar ratio of 1:1:1:1:1 to make the total salt concentration 1.5M. A magnetic heating stirrer was used to stir at 40°C for 8 hours to fully dissolve the lithium salt to form a homogeneous solution to obtain a high entropy electrolyte. At room temperature, the electrolyte system was used for full battery testing with silicon carbon as the negative electrode and lithium iron phosphate as the positive electrode. After testing, it was found that the coulombic efficiency of the battery can reach 99.6%, and at 0.815mA cm 2- At a current density of 1.54 W, its cycle life can reach 1200 cycles, and the capacity retention rate is above 80%.

[0074] Embodiment 10:

[0075] This embodiment provides a high entropy electrolyte for a lithium ion battery:

[0076] Ethylene carbonate, methyl propionate, and accompanying ethylene carbonate were mixed in a volume ratio of 3:6:1, and lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium trifluoromethanesulfonate, and lithium trifluoroacetate were added to an organic solvent in a molar ratio of 1:1:1:1:1 to make the total salt concentration 1.0M. A magnetic heating stirrer was used to stir at 40°C for 8 hours to fully dissolve the lithium salt to form a homogeneous solution to obtain a high entropy electrolyte. The electrolyte system was used for full battery testing with graphite as the negative electrode and lithium nickel cobalt manganese oxide as the positive electrode. After testing, it was found that the coulombic efficiency of the battery can reach 98.9%, and at 0.815mA cm 2- Its cycle life can reach 400 cycles at a current density of 1.58kWh, and the capacity retention rate is over 90%.

[0077] Embodiment 11:

[0078] This embodiment provides a high entropy electrolyte for a lithium ion battery:

[0079] Ethylene carbonate, methyl propionate, and accompanying ethylene carbonate were mixed in a volume ratio of 3:6:1, and lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium trifluoromethanesulfonate, lithium trifluoroacetate, and lithium nitrate were added to an organic solvent in a molar ratio of 1:1:1:1:1 to make the total salt concentration 1.0M. A magnetic heating stirrer was used to stir at 40°C for 8 hours to fully dissolve the lithium salt to form a homogeneous solution to obtain a high entropy electrolyte. The electrolyte system was used for full battery testing with silicon graphite as the negative electrode and lithium iron phosphate as the positive electrode. After testing, it was found that the coulombic efficiency of the battery can reach 99.7%, and at 0.815mA cm 2- At a current density of 1.54 W, its cycle life can reach 1100 cycles, and the capacity retention rate is above 85%.

[0080] Embodiment 12:

[0081] This embodiment provides a high entropy electrolyte for a lithium ion battery:

[0082] Ethylene carbonate, methyl propionate, and accompanying ethylene carbonate were mixed in a volume ratio of 3:6:1, and lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium trifluoromethanesulfonate, lithium trifluoroacetate, and lithium nitrate were added to an organic solvent in a molar ratio of 1:1:1:1:1 to make the total salt concentration 1.5M. A magnetic heating stirrer was used to stir at 40°C for 8 hours to fully dissolve the lithium salt to form a homogeneous solution to obtain a high entropy electrolyte. At room temperature, the electrolyte system was used for full battery testing with silicon oxide as the negative electrode and lithium iron phosphate as the positive electrode. After testing, it was found that the coulombic efficiency of the battery can reach 99.2%, and at 0.815mA cm 2- Its cycle life can reach 500 cycles at a current density of , and the capacity retention rate is above 80%.

[0083] Embodiment 13:

[0084] This embodiment provides a high entropy electrolyte for a lithium ion battery:

[0085] Ethylene carbonate and ethylene glycol dimethyl ether were mixed in a volume ratio of 1:1, and lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, and lithium tetrafluoroborate were added to an organic solvent in a molar ratio of 1:1:1:1:1 to make the total salt concentration 1.0M. A magnetic heating stirrer was used to stir at 40°C for 8 hours to fully dissolve the lithium salt to form a homogeneous solution to obtain a high entropy electrolyte. At room temperature, the electrolyte system was used for full battery testing with silicon negative electrode and lithium manganese iron phosphate as the positive electrode. After testing, it was found that the coulombic efficiency of the battery can reach 99.3%, and at 0.815mA cm 2-Its cycle life can reach 400 cycles at a current density of 1.58kWh, and the capacity retention rate is above 85%.

[0086] Verification Example 1:

[0087] The conventional electrolyte used in the verification example is a mixed solvent prepared by dissolving 1.0M lithium hexafluorophosphate in ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7.

[0088] The positive and negative electrodes with matching capacity were assembled into NCM523 / graphite full cells (positive electrode loading: 10.5 mg / cm 2 ) Using a Xinwei battery tester to perform a constant current intermittent titration test (GITT), it was found that the polarization voltage of the battery using a high entropy electrolyte during the process of returning to the equilibrium potential after a cycle of current pulses was lower than that of the conventional electrolyte ( Figure 1 ). And the lithium ion diffusion coefficient fitted by this test method is higher than that of conventional electrolyte ( Figure 2 ), using the three-electrode method to perform cycle tests on full batteries using different electrolytes ( Figure 3 ), it can be seen that the polarization voltage that the high entropy electrolyte needs to overcome to reach the charging platform is smaller than that of the conventional electrolyte. Its lower lithium ion diffusion migration energy barrier ensures that it has a more excellent lithium ion kinetic migration process and fast charging characteristics.

[0089] The assembled full battery was placed on a battery charge and discharge instrument for rate cycle testing. The battery rate test used 0.1C, 0.5C, 1C, 2C, 4C, 5C, and 10C rates, with each rate cycled 5 times. It can be found that the rate performance of the high entropy electrolyte is much higher than that of the conventional electrolyte ( Figure 4 ). The cycled battery was disassembled and the negative electrode was tested by SEM ( Figure 5 ). It can be seen that compared with conventional electrolytes (left), the graphite anode of the battery using high-entropy electrolytes (right) presents more complete graphite particles, and the conventional electrolyte even exhibits lithium precipitation under the test conditions, which shows that high-entropy electrolytes can still achieve rapid and reversible insertion and deinsertion of lithium ions in the graphite anode under fast charging conditions and maintain the stability of the electrode structure.

[0090] The full battery that had been cycled for 400 cycles at 0.5C current was disassembled and the positive electrode was tested by SEM ( Figure 6 ), it can be found that the conventional electrolyte (left) has obvious cracks in the positive electrode structure due to the attenuation mechanism of cyclic aging, while the high-entropy electrolyte still maintains a relatively smooth and complete electrode structure.

[0091] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A high entropy electrolyte for lithium ion batteries, characterized in that: The high entropy electrolyte for lithium-ion batteries is composed of a variety of lithium salts and organic solvents, and is used to improve the kinetic migration process of lithium ions in the electrolyte; The organic solvent is at least one of an ester solvent, an ether solvent, and an ether-ester blend solvent; The total concentration of various lithium salts in organic solvents is 1.0-2.0 mol / L; The lithium salt is selected from at least five of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium trifluoroacetate, and lithium nitrate.

2. A high entropy electrolyte for lithium ion batteries according to claim 1, characterized in that: The organic solvent is selected from at least two or more of vinylene carbonate, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, triethyl phosphate, trimethyl phosphate, ethyl methyl carbonate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, ethyl butyrate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and 1,3-dioxolane.

3. A high entropy electrolyte for lithium ion batteries according to claim 1, characterized in that: The lithium salt in the electrolyte promotes the decomposition of the organic solvent on the surface of the negative electrode to form an SEI rich in F, B, P, S, and N inorganic components, so that the lithium battery adapted to the electrolyte has excellent fast charging performance at room temperature.

4. A high entropy electrolyte for lithium ion batteries according to claim 1, characterized in that: The water content in the high entropy electrolyte for lithium-ion batteries is less than 1 ppm.

5. A method for preparing a high entropy electrolyte for a lithium ion battery as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: In an inert argon atmosphere, the lithium salt and the organic solvent in the high entropy electrolyte for lithium ion batteries are evenly mixed to obtain the high entropy electrolyte for lithium ion batteries.

6. The method for preparing a high entropy electrolyte for a lithium ion battery according to claim 5, characterized in that: The specific process of uniformly mixing the lithium salt and the organic solvent in the high entropy electrolyte for lithium-ion batteries is as follows: mixing the organic solvent and the lithium salt, and stirring at 40° C. for 8 hours using a magnetic heating stirrer to fully dissolve the lithium salt to form a homogeneous solution.

7. A battery, characterized in that: The electrolyte used in the battery is the high entropy electrolyte for lithium ion battery according to any one of claims 1 to 4 or the high entropy electrolyte for lithium ion battery prepared by the method for preparing a high entropy electrolyte for lithium ion battery according to claim 5.

8. A battery according to claim 7, characterized in that: The positive electrode of the battery includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide; The negative electrode of the battery includes one or more of graphite, hard carbon, silicon negative electrode, silicon-carbon negative electrode, silicon-graphite negative electrode, and silicon monoxide.

9. A battery according to claim 7, characterized in that: The separator of the battery is one of polyethylene, polypropylene, PP / PE / PP three-layer composite film and glass fiber separator.

10. A battery according to claim 7, characterized in that: The positive and negative electrode capacities of the battery are matched, that is, the ratio of the negative electrode capacity to the positive electrode capacity of the battery is 1.10-1.15.